Developing Criteria of an English Textbook Evaluation for Indonesian Senior High School - Sirajul Munir; Nina Suzanne; Yulnetri Yulnetri (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2021)
The use of criteria of an English textbook is crucial to improve the quality of teaching. However, choosing the criteria is a challenging task for teachers and material developers. This recent study aims at developing criteria of an English textbook evaluation for Indonesian Senior High School. This research used Research and Development. Three phases were employed: exploration stage, development stage, and validation stage. At the exploration stage, 17 respondents of English teachers were asked about the need of developing the criteria of the English textbook. All respondents agreed that the textbook evaluation criteria were needed since there is no particular standardized textbook evaluation available. Therefore, they need to use the criteria as the basis to determine the quality of a particular textbook. At the development stage, 10 criteria to evaluate textbooks were constructed. Those cover (1) aims and approaches; (2) design and organization; (3); content; (4) skills; (5) vocabulary; (6) exercises and activities; (7) methodology; (8) attractiveness of the textbook and physical make-up; (9) teacher’s manual; and (10) practical consideration. At the validation stage, the textbook evaluation criteria were deemed valid by experts. Considering these facts, 10 designed criteria could be used as the principle to determine an evaluation of English textbooks, primarily in the teaching English at Indonesian Senior High school.